The association between first-time accreditation and the delivery of recommended care: a before and after study in the Faroe Islands - Maria Daniella Bergholt; Anne Mette Falstie-Jensen; Peter Hibbert; Barbara Joensen Eysturoy; Gunnvá Guttesen; Tóra Róin; Jan Brink Valentin; Jeffrey Braithwaite; Christian von Plessen; Søren Paaske Johnsen (BMC, 2021)
Abstract Background Significant resources are spent on hospital accreditation worldwide. However, documentation of the effects of accreditation on processes, quality of care and outcomes in healthcare remain scarce. This study aimed to examine changes in the delivery of patient care in accordance with clinical guidelines (recommended care) after first-time accreditation in a care setting not previously exposed to systematic quality improvement initiatives. Methods We conducted a before and after study based on medical record reviews in connection with introducing first-time accreditation. We included patients with stroke/transient ischemic attack, bleeding gastric ulcer, diabetes, chronic obstructive pulmonary disease (COPD), childbirth, heart failure and hip fracture treated at public, non-psychiatric Faroese hospitals during 2012-2013 (before accreditation) or 2017-2018 (after accreditation). The intervention was the implementation of a modified second version of The Danish Healthcare Quality Program (DDKM) from 2014 to 2016 including an on-site accreditation survey in the Faroese hospitals. Recommended care was assessed using 63 disease specific patient level process performance measures in seven clinical conditions. We calculated the fulfillment and changes in the opportunity-based composite score and the all-or-none score. Results We included 867 patient pathways (536 before and 331 after). After accreditation, the total opportunity-based composite score was marginally higher though the change did not reach statistical significance (adjusted percentage point difference (%): 4.4%; 95% CI: − 0.7 to 9.6). At disease level, patients with stroke/transient ischemic attack, bleeding gastric ulcer, COPD and childbirth received a higher proportion of recommended care after accreditation. No difference was found for heart failure and diabetes. Hip fracture received less recommended care after accreditation. The total all-or-none score, which is the probability of a patient receiving all recommended care, was significantly higher after accreditation (adjusted relative risk (RR): 2.32; 95% CI: 2.03 to 2.67). The improvement was particularly strong for patients with COPD (RR: 16.22; 95% CI: 14.54 to 18.10). Conclusion Hospitals were in general more likely to provide recommended care after first-time accreditation.